Back Cover: Synthesis of PAF, an Antifungal Protein from P. chrysogenum, by Native Chemical Ligation: Native Disulfide Pattern and Fold Obtained upon Oxidative Refolding (Chem. Eur. J. 38/2013). Issue 38 (12th September 2013) - Váradi, Györgyi; Tóth, Gábor K.; Kele, Zoltán; Galgóczy, László; Fizil, Ádám; Batta, Gyula
<x xml:space="preserve">Abstract</x> PAF, an antifungal protein found in P. chrysogenum, is stabilized with three disulfide bonds that are essential for bioactivity. G. Váradi, G. K. Tóth and co‐workers in their Full Paper on page 12684 ff. show that the protein with its native fold and disulfide pattern can be prepared in good yield by using a combination of solid‐phase synthesis and native chemical ligation followed by oxidative refolding.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>